2022
DOI: 10.3390/ijerph191912712
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Perception towards Organic Products before and after the COVID-19 Pandemic: A Case Study in Bihor County, Romania

Abstract: Organic products have grown ever more popular in recent years due to increased concerns regarding one’s health, the environment, and sustainability. The COVID-19 pandemic has only accelerated this growth, prompting producers to adapt to a rapidly growing market while maintaining the same standard of quality. We have conducted a questionnaire-based pilot study on 190 organic food consumers from Bihor county, Romania, in order to analyze the main factors influencing customers’ beliefs regarding organic food cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…Food consumption patterns are continuously shaped by consumers' preferences with an increasing trend toward healthier and more sustainable foods (Nunes et al, 2020). This trend was also noticed in Romania in the last years (Muresan et al, 2021, Radulescu et al, 2021, Brata et al, 2022 regarding both fresh and processed food products. It is understandable that consumers play an incontestable role as they influence the demand of products through their buying behavior (Dibb et al, 2012), while producers face challenges when offering "the right product in the right place, at the right price, at the right time" (Neck et al, 2018(Neck et al, , p.1190.…”
Section: Introductionmentioning
confidence: 83%
“…Food consumption patterns are continuously shaped by consumers' preferences with an increasing trend toward healthier and more sustainable foods (Nunes et al, 2020). This trend was also noticed in Romania in the last years (Muresan et al, 2021, Radulescu et al, 2021, Brata et al, 2022 regarding both fresh and processed food products. It is understandable that consumers play an incontestable role as they influence the demand of products through their buying behavior (Dibb et al, 2012), while producers face challenges when offering "the right product in the right place, at the right price, at the right time" (Neck et al, 2018(Neck et al, , p.1190.…”
Section: Introductionmentioning
confidence: 83%
“…24 According to a study conducted by Brata et al, in 2022 on consumers' perceptions of organic food products during the COVID-19 pandemic, there was an increased awareness among people about the products they purchase. 25 This led to an increased consumption of organic food due to its perceived higher quality, nutritional value, and environmental friendliness compared to other food products. The findings of the current study support previous research in this area, which identified key factors that influence consumers' decisions to buy organic products.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Nguyen and Phan [ 70 ] showed that consumers in Vietnam with a high level of COVID-19 anxiety presented high degrees of health consciousness and purchasing intention of functional foods. Brata et al [ 71 ] revealed that the pandemic has accelerated individual’s interest in organic food products’ attributes and values, as organic foods are generally regarded to be safer, healthier, and more pro-environmental than conventional foods [ 36 ]. Thus, we intend to investigate the impact of IOC on Chinese consumers’ PVOF, health consciousness, and continuous organic food purchase intentions during the pandemic.…”
Section: Theoretical Framework and Development Of Hypothesesmentioning
confidence: 99%